Hubungan antara Waktu Tindakan Intubasi dengan Outcome Pasien Stroke di RSUP Prof. Dr. R. D. Kandou Manado: Kajian terhadap Glasgow Coma Scale, Ventilator Associated Pneumonia, Length of Stay, dan Angka Kematian - Poluan, Timothy M.; Lalenoh, Diana C. H.; Kambey, Barry I. (Universitas Sam Ratulangi, 2018)
Abstract: Stroke patients with decreased consciousness, airway disorders, hypoxia, apnea or therapeutic initiation of hyperventilation must be intubated. The delay in intubation time in stroke patients with a deteriorating general condition is very dangerous because it is related to higher mortality within the first 24 to 48 hours and will affect the length of stay (LOS). One of the indications for intubation in stroke patients is the decrease in consciousness, namely the Glasgow Coma Scale (GCS) score <9. Albeit, intubation and mechanical ventilation can cause a person 6 to 21 times more likely to develop pneumonia, commonly referred to as ventilator associated pneumonia (VAP). This study was conducted at Prof. Dr. R. D. Kandou Hospital Manado and was aimed to obtain the correlation between time of intubation and stroke patient’s outcome based on GCS, VAP, LOS, and mortality. The results showed that there was no relationship between time of intubation <48 hours or ≥48 hours after stroke and improvement of GCS (0%); between time of intubation <48 hours or ≥48 hours after stroke and the occurence of VAP (P=0.698); and between time of intubation <48 hours or ≥48 hours after stroke and LOS (r=0.265; P=0.054); as well as between time of intubation <48 hours or ≥48 hours after stroke and mortality in the first two days after intubation (P=0.313).Keywords: stroke, time of intubation, outcome. Abstrak: Pasien stroke dengan penurunan kesadaran, gangguan jalan napas, hipoksia, apnea atau inisiasi terapetik hiperventilasi harus diintubasi. Penundaan waktu tindakan intubasi pada pasien stroke dengan keadaan umum yang memburuk sangat berisiko karena berkaitan dengan mortalitas dalam waktu 24-48 jam pertama dan akan memengaruhi length of stay (LOS). Indikasi dilakukannya intubasi terhadap pasien stroke salah satunya ialah penurunan kesadaran yang dinilai dengan skor Glasgow Coma Scale (GCS) <9. Intubasi dan ventilasi mekanik dapat menyebabkan seseorang 6 sampai 21 kali lipat cenderung terkena pneumonia (ventilator associated pneumonia/VAP). Penelitian ini bertujuan untuk mendapatkan hubungan antara waktu tindakan intubasi dengan outcome pasien stroke di RSUP Prof. Dr. R. D. Kandou Manado dengan menggunakan kajian terhadap GCS, VAP, LOS, dan angka kematian. Hasil penelitian memperlihatkan tidak terdapat hubungan antara waktu tindakan intubasi <48 jam atau ≥48 jam setelah serangan stroke dengan perbaikan GCS (0%); dengan kejadian VAP (P=0,698); dengan LOS (r=0,265; P=0,054); dan dengan angka kematian pada 2 hari pertama setelah diintubasi (P=0,313).Kata kunci: stroke, waktu tindakan intubasi, outcome